747 Suicidal Ideation Associated with Cognitive Hyperarousal, Rumination and Insomnia in Depressed Perinatal Women. (3rd May 2021) - Arnett, Lily; Kalmbach, David; Ahmedani, Brian; Gelaye, Bizu; Drake, Christopher; Cheng, Philip
Abstract: Introduction: This prospective study explored associations among clinical insomnia, nocturnal cognitive hyperarousal, and nocturnal perinatal-focused rumination with suicidal ideation (SI) in perinatal women with mild-to-moderate depression. Methods: From late pregnancy through early postpartum, 39 women with depression completed 17 weekly surveys assessing insomnia, depression, suicidal ideation, perceived stress, and three cognitive arousal indices. Results: Women with nocturnal cognitive hyperarousal at baseline, relative to those with low nocturnal cognitive arousal, were at greater risk for developing new onset SI in late pregnancy or early postpartum (33% vs 1%). Moreover, nocturnal perinatal-focused rumination was independently associated with SI. SI-risk was highest when women reported clinical insomnia combined with nocturnal cognitive hyperarousal (OR=5.66, p=.037) or perinatal-focused rumination (OR=11.63, p=.018). Daytime perseverative thinking was not uniquely associated with SI. Conclusion: Cognitive hyperarousal and perinatal-focused rumination at night are uniquely associated with SI among perinatal women with depression. Moreover, insomnia augments the suicidogenicity of nighttime cognitive activity. Future research should determine whether alleviating nocturnal cognitive arousal, pregnancy- and fetal/infant-related concerns, and insomnia with psychotherapy reduces SI for women with perinatal depression. Support (if any): This study was funded by the American Academy of Sleep Medicine (198-FP-18, PI: Kalmbach). Dr. Cheng's effort was supported by the National Heart, Lung, and Blood Institute (K23-HL13866, PI: Cheng).